Developing an Integrated Marketing Communication Model to Enhance International Students’ Interest in Indonesian Sharia Investments - Andi Mappatompo; A.Ifayani Haanurat; Sukmawati -; Zalkha Soraya; Sahabuddin Nanda; Muchriana Muchran; Wa Ode Rayyani; Asri Jaya; M. Yusuf K (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This community engagement programme (INTERNATIONAL COMMUNITY SERVICE) aims to develop and implement an Integrated Marketing Communication (IMC) model to enhance international students' interest in Indonesian Sharia investment products. The programme was held at Al-Azhar University in Cairo and targeted 30 international students with educational backgrounds closely related to Islamic studies. The initiative responds to the growing potential of Indonesia's Sharia capital market and the need for effective global communication strategies to promote Islamic financial products. The programme applied a combination of educational seminars, digital campaigns, and interactive discussions designed to improve students' awareness, understanding, trust, and investment interest. A pre-test and post-test survey method was used to measure the effectiveness of the IMC approach. The results indicate significant improvements across all measured indicators. Awareness of Indonesian Sharia investment products showed the highest increase, followed by improvements in understanding of Sharia investment concepts, trust in Indonesian Sharia financial institutions, and interest in investing in Sharia-compliant products. The findings demonstrate that integrating educational content with persuasive and value-based communication is effective in promoting Islamic financial products among international students. Digital media also played an important role in reinforcing messages and sustaining engagement beyond face-to-face activities. The programme confirms that an IMC model tailored to Indonesia's cultural and religious values can serve as a practical strategy to expand the global reach of Indonesia's Sharia capital market, particularly within international academic communities. Contribution to Sustainable Development Goals (SDGs):SDG 4 : Quality Education; SDG 8 : Decent Work and Economic Growth; SDG 10 : Reduced Inequalities; SDG 12 : Responsible Consumption and Production